Desenvolvimento participativo de produtos turísticos em terras indígenas na Amazônia brasileira - Schneider, Alessandra Helena; Alvarenga, Fernanda (Revista Brasileira de Ecoturismo (RBEcotur), 2015)
O artigo apresenta a metodologia criada e experimentada para o planejamento participativo de produtos turísticos em terras indígenas e os principais resultados de sua aplicação. O turismo foi identificado pelos indígenas como uma atividade econômica alternativa ao desmatamento durante o desenvolvimento dos Planos de Gestão Territorial na Terra Indígena Sete de Setembro (RO/MT) do Povo Paiter-Suruí e na Terra Indígena Nove de Janeiro (AM) do Povo Parintintin. Com o objetivo de propor princípios e procedimentos para visitação turística ordenada, o processo de planejamento participativo buscou garantir que, além de ser uma alternativa economicamente viável, o turismo seja também um instrumento de resgate e valorização cultural, que respeita a diversidade, mitos, cosmovisão e modo de vida atual indígena. A metodologia utilizada para o desenvolvimento dos produtos turísticos envolveu uma série de atividades como oficinas de turismo, intercâmbio, inventários, planejamento de roteiros, propostas de infraestrutura e estudos de mercado específicos para cada uma das etnias. Como resultado obteve-se propostas de operações turísticas viáveis e adequadas ao mercado, mas que também atendem às expectativas e possibilidades dos indígenas. Estas experiências também resultaram em uma metodologia de desenvolvimento de produtos turísticos estruturada na relação entre o saber científico e tradicional, portanto em uma dinâmica participativa, que poderá contribuir para a regulamentação da atividade turística em Terras Indígenas, adequando-se à Política Nacional de Gestão Ambiental e Territorial Indígena. Participative development of tourism products in indigenous lands located in the brazilian Amazon ABSTRACT The article presents the methodology created and experimented for participative planning applied in the development of tourism products in indigenous lands and the principal results obtained. During the development process of the Territorial Management Plans for the Sete de Setembro Indigenous Land, belonging to Paiter-Suruí People (States of Roraima and Mato Grosso) and for the Nove de Janeiro Indigenous Land, belonging to Parintintin People (Amazonas State), tourism was identified by the indigenous peoples themselves as being a viable alternative economic activity to deforestation. With the aim of proposing standards and procedures for organized guided tours, this project sought to guarantee that, in addition to representing a viable economic alternative, tourism should also function as a means of valuing and reviving traditional indigenous culture, in a way that respects the diversity, mythology, worldview and the way of life of tribal peoples today. The methodology of development of tourism products involved a series of activities, such as tourism workshops, interchange, register, planning tourist routes, proposals related to infrastructure and market studies specifically designed for each ethnic group. The results of this work are proposes of viable tourism operations, those also fulfils the expectations and possibilities of the Indigenous peoples themselves. These experiences resulted in a methodology of developing tourism products based on a relationship between scientific and traditional knowledge, consequently using a participative approach, which may be useful when regulating tourism activities in Tribal Lands, in accordance with Brazil’s National Policy for the Territorial and Environmental Management of Indigenous Lands. KEYWORDS: Tourism in Indigenous Lands; Participative Planning; Sustainability; Tourism Goods; Brazilian Amazon.